Pengaruh Store Atmosphere (Suasana Toko) Terhadap Keputusan Pembelian Impulsif (Studi Pada Ace Hardware Mall Olympic Garden Malang) - Munandar, Kahfi; Rohman, Fatchur (Jurnal Ilmiah Mahasiswa FEB, 2016)
Store atmosphere is a combination of physical characteristics such store architecture, layout, lighting, display, color, room temperature, music, aroma thoroughly will create the image in the minds of consumers. This study aims to determine the influence of ambient factors (X1), social factors (X2) and factor design (X3) against impulsive buying decision (Y) at Ace Hardware MOG Malang. This research is an explanatory research that explains the causal relationships between variables through hypothesis testing. This study used a sample of 130 respondents drawn from the customer population Ace Hardware MOG. Sampling using purposive sampling technique and roscoe. Test equipment used, among others, validity, reliability, and classical assumption. Hypothesis testing is done using t-test and F test data were analyzed using multiple linear regression analysis. Based on the results of the F test was found that the variable ambient factors, social factors and design factors influence simultaneously on impulsive buying decisions. Then based on the results of the t test found that variable ambient factors, social factors and design factors partial effect on impulsive buying decisions. Variable ambient factors, social factors, and design factors significantly influence impulsive buying decisions, which means these three factors influence the decision to increase impulse purchases While based on the standardized Î² coefficient was found that the variables are dominant design factor influencing customer satisfaction variable of 0.312. Keywords: Store Atmosphere, Ambien factors, social factors, Factor Design, impulse nuying decision